ความรุนแรงต่อภรรยาของผู้ป่วยโรคจิตเภทที่ดื่มสุราตามการรับรู้ของภรรยา The Prevalence of Violence against the Wives of the Schizophrenic Patients with Alcohol Use: Perception of Their Wives - ศรีโอษฐ์ พัฒนี; แสวงเจริญ กฤตยา (วารสารการพยาบาลและการดูแลสุขภาพ, 2016)
การวิจัยเชิงพรรณนานี้ มีวัตถุประสงคเ์ พื่อศึกษาความชุกของความรุนแรงตอ่ ภรรยาของผูป้ ว่ ยโรคจิตเภทที่ ดื่มสุราตามการรับรู้ของภรรยา ลักษณะความรุนแรงต่อภรรยา และผลกระทบของความรุนแรงในครอบครัวของ ผู้ป่วยโรคจิตเภทที่ดื่มสุรา กลุ่มตัวอย่าง คือภรรยาของผู้ป่วยโรคจิตเภทที่ดื่มสุรา จำนวน 96 คน เก็บข้อมูลด้วย แบบสอบถามความรุนแรงตอ่ ภรรยาของผูป้ ว่ ยโรคจิตเภทที่ดื่มสุรา หาความเที่ยงโดยใชสั้มประสิทธิ์อัลฟา่ ของครอ นบาค ได้ค่าเท่ากับ .89 วิเคราะห์ข้อมูลโดยหาความถี่ ร้อยละ ค่าเฉลี่ย ค่ามัธยฐาน ส่วนเบี่ยงเบนมาตรฐาน 95% CI และ Fisher’s exact test ผลการวิจัย พบว่ากลุ่มผู้ป่วยโรคจิตเภทที่ดื่มสุราทุกวัน มีความรุนแรงต่อภรรยา ร้อยละ 98.0 ไม่ดื่มทุกวันมีความรุนแรงต่อภรรยา ร้อยละ 80.0 เมื่อเปรียบเทียบความรุนแรงต่อภรรยาระหว่างกลุ่มที่ดื่มสุราทุกวันกับไม่ดื่มทุกวัน พบผลต่าง ร้อยละ 18 (95% CI; 5.7 - 30.3) อย่างมีนัยสำคัญทางสถิติที่ระดับ p-value 0.005 ความชุกความรุนแรงต่อภรรยาของผู้ป่วยโรคจิตเภทที่ดื่มสุราตามการรับรู้ของภรรยา พบร้อยละ 89.6 (95% CI; 81.7 - 95.0)พบมาก คือสามีกล่าวโทษว่าภรรยามีความสัมพันธ์กับชายอื่น ความรุนแรงด้านจิตใจอารมณ์ ร้อยละ 60.4 (95%CI; 49.9 - 70.3) พบมาก คือสามีแสดงอารมณ์เกรี้ยวกราดต่อภรรยา ความรุนแรงด้านร่างกาย ร้อยละ 47.9 (95%CI; 37.6 - 58.3) พบมาก คือสามีทำลายข้าวของหรือขว้างปาเวลาโกรธ และความรุนแรงด้านการเงินและทรัพย์สินร้อยละ 26.0 (95% CI; 17.6 - 36.0) พบมาก คือสามีแย่งหรือขโมยทรัพย์สินไปเพื่อกินเหล้า/เล่นการพนัน ผลกระทบของความรุนแรงในครอบครัวของผูป้ ว่ ยโรคจิตเภทที่ดื่มสุรา คือภรรยามีความทุกขใ์ จ ไมมี่ความสุขในชีวิตครอบครัวต้องการหย่าร้างเมื่อมีโอกาส มีการภาคทัณฑ์กัน ได้รับการบาดเจ็บทางกาย และลูกๆมีการเรียนตกตํ่าลง/เกเร หรือมีพฤติกรรมไม่พึงประสงค์สรุปวา่ กลุม่ ผูป้ ว่ ยโรคจิตเภทที่ดื่มสุราทุกวันมีความรุนแรงตอ่ ภรรยาสูงกวา่ กลุม่ ที่ไมดื่มทุกวัน ดังนั้นผูป้ ว่ ยโรคจิตเภทที่ดื่มสุราควรได้รับการประเมินปัญหา และวางแผนการพยาบาล เพื่อช่วยเหลือ ป้องกัน และแก้ไขปัญหาความรุนแรงในครอบครัว This study was a descriptive study which aimed to investigate the prevalence of violence against the wives of the schizophrenic patients with alcohol use according to the perception of the wives, the nature of violence against the wives and the effects of domestic violence of the schizophrenic patients who drank alcohol. The samples were 96 wives of the schizophrenic patients who drank alcohol. The reliability of the research tool was verified by Cronbach Alpha Coefficient and its reliability was .89. The data were analyzed by percentage, mean, median and standard deviation, 95% CI and Fisher’s exact test. The results showed as the followings. When considering the frequency of alcohol drinking, it was found that the husbands who drank alcohol every day caused the violence as of 98.0 percent while those who did not drink alcohol every day caused the violence as of 80.0 percent. The prevalence of the violence of the schizophrenic patients who drank alcohol every day was different from the schizophrenic patients who did not drink alcohol every day 18 percent (95% CI; 5.7 - 30.3, p-value 0.005). The prevalence of violence against the wives of schizophrenic patients with alcohol use according to the perception of the wives was 89.6 (95% CI; 81.7 - 95.0). Mostly, the wives were accused of having affair with other men by their husbands. The sexual violence was 89.6 (95% CI; 81.7 - 95.0). The psychological and emotional violence was 60.4 (95% CI; 49.9 - 70.3). It was mostly found that the husbands were always enraged (fighting with wives). The physical violence was 47.9 (95% CI; 37.6 - 58.3), which the husbands always threw or broke things when they were angry. The financial and property violence was 26.0 (95% CI; 17.6 - 36.0). The husband mostly grabbed or stole money or property for buying alcohol / gambling. The first five impacts of the domestic violence of the schizophrenic patients who drank alcohol were that the wives were distressed as of 64.6 percent, followed by having an unhappy family life which was 62.5 percent and requiring getting divorce when having chances which was 60.4. There was also probation. For example, if there was domestic violence again, the couples would be separated (52.1 percent). These also included having physical injuries such as bruises or the study’s results of the children were lower /the children were unruly or having unwanted behaviors (33.3 percent). The results of this study showed that the schizophrenic patients drinking alcohol caused violence towards their wives, and there were also the impacts on families. Therefore, the attention should be provided to these patients. Also, the assessment or screening and helping to reduce domestic violence are required.